Optimal Portfolio Analysis Using the Markowitz Model and Single Index Model on Jakarta Islamic Index (JII) Stocks: Historical Data 2022–2025 - Cahaya Ningsih; Pipit Yunianingsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes and compares the construction of optimal Islamic stock portfolios using the Markowitz Model and the Single Index Model for stocks listed in the Jakarta Islamic Index (JII). The dataset consists of monthly closing prices of 30 JII constituent stocks from January 2022 to December 2025. A quantitative approach with purposive sampling is applied, in which only stocks with positive expected returns and positive excess returns are selected. The Sukuk Ritel SR023T3 rate of 5.8% per year is used as the risk-free benchmark. Data processing and portfolio optimization are conducted using Microsoft Excel Solver. Using the Markowitz Model with minimum risk preference, the optimal portfolio comprises nine stocks ASII, BRIS, JPFA, PGAS, ANTM, TPIA, MEDC, DSSA, and INKP producing an expected annual return of 16.29% with a minimum risk level of 51.94%. When optimized using the Sharpe Ratio, the model generates a portfolio of eleven stocks with a higher expected return of 33.21% and a corresponding risk of 64.04%. Under the Single Index Model, the optimal portfolio consists of PANI, TPIA, and BRMS, with respective weights of 66.08%, 25.82%, and 8.09%. This portfolio yields a significantly higher expected annual return of 144.97% with a beta of 1.8945, indicating greater systematic risk.